Isaiah Shavitt A Memorial Festschrift from Theoretical Chemistry Accounts - Shepard, Ron.; Pitzer, Russell M.; Dunning, Thom.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
In this Festschrift dedicated to the late Isaiah Shavitt (1925-2012) , selected researchers in theoretical chemistry present research highlights on major developments in the field. Originally published in the journal Theoretical Chemistry Accounts, these outstanding contributions are now available in a hardcover print format, as well as a special electronic edition. This volume provides valuable content for all researchers in theoretical chemistry, and will especially benefit those research groups and libraries with limited access to the journal.
From the Contents: The Second Order Ehrenfest Method A Practical CASSCF Approach to Coupled Electron-Nuclear Dynamics -- Anchoring the Potential Energy Surface for the Br + H2O → HBr + OH Reaction -- Isaiah Shavitt - Computational Chemistry Pioneer.-Comparison of one-dimensional and quasi-one-dimensional Hubbard models from the variational two-electron reduced-density-matrix method -- Steric and electrostatic effects on photoisomerization dynamics using QM/MM ab initio multiple spawning.
Keywords: Chemistry, Physical and theoretical; Atomic structure .; Molecular structure .; Physical chemistry; Theoretical Chemistry; Atomic and Molecular Structure and Properties; Physical Chemistry